Rheological characterization of CNC-CTAB network below and above critical micelle concentration (CMC). (1st April 2021) - Gahrooee, Tina Raeisi; Abbasi Moud, Aref; Danesh, Marziyeh; Hatzikiriakos, Savvas G.
Graphical abstract: Highlights: CNC-CTAB gels show diminishing thixotropic behavior as a function of CTAB. They exhibit single and two yielding maxima as a function of CTAB above CMC of CTAB. CNC gel showed a continuous yielding region using steady, oscillatory and creep testing. Different network below and above the CMC of CTAB was found rheologically. Abstract: The network of Cellulose Nanocrystal (CNC) suspension is explored below and above the critical micelle concentration (CMC), in the presence of cetyltrimethylammonium bromide (CTAB) with a positively charged head using TEM imaging and rheological characterization. CNC-CTAB gels show shear thinning behavior, complex relationship between strain amplitudes and CTAB concentration, diminishing thixotropic behavior as a function of CTAB and single and two yielding stress maxima as a function of CTAB, resulting from different microstructure below and above the critical Micelle Concentration (CMC) of CTAB. Comparing the flow curves of CNC-CTAB suspension/gel revealed the role played by CTAB content, CNC concentration and sonication energy in strengthening of the network. We analyzed and obtained yield stress from steady shear, creep testing and oscillatory experiments and compared them.